Environmental Politics: Grassroots Innovations in Conserving Geopark Environment (Study in Gunung Sewu UNESCO Global Geopark) - Sulistyo, Ari; Rijanta, Rijanta; Hadna, Agus Heruanto; Giyarsih, Sri Rum (Jurnal Politik Indonesia: Indonesian Political Science Review, 2021)
Environmental damage is the real threat of natural resources where the economic motives (utility) are often contrary to the conservation motives (protection). However, there are some efforts to reduce the damage. One of them is called bottom-up innovation, which is known as grassroots innovation. This study aims to identify and analyze the innovations emerging from society to preserve the environment in the geopark area, which is used as tourism objects. It is a qualitative descriptive study conducted on Nglanggeran Ancient Volcano Geosite, Pindul Cave Geosite, and Siung Beach Geosite. This study shows that the grassroots innovations are not purely initiated by local communities but by some people who are members of tourism awareness groups or Pokdarwis. The innovations were carried out independently without the help of experts or the government, the innovations were developed by a â€œtrial and errorâ€ process, and the innovations are temporary and sometimes only solve the current problems and local scope. Based on the implication, the grassroots innovations can be divided into two categories; direct influence or indirect influence.Â